Criação de conhecimento em acordos de cooperação interorganizacionais com uso e geração de dados abertos: caso de estudo UTFPR - Benelli, Ana Carolina (2019)
In the last three decades the higher education institutions have contributed significantly to the creation of knowledge in interorganizational cooperative environments, bringing important input to the construction of an environment of territorial interaction. The central theme of this dissertation is the knowledge creation in interorganizational cooperation agreements between government, industry and academia. This study has the general objective of mapping the process of knowledge creation, and its archetypes, in these agreements, especially in those that use and generate open data. It is an applied research, with case study based on the results generated in cooperation agreements of the Universidade Tecnológica Federal do Paraná (UTFPR). Semi-structured interviews and documentary research were used as primary data generation techniques, supported by Content Analysis as the main method, therefore this research was mostly qualitative. The main results reported the correlation of Cooperative Interorganizational Relation Processes with the Five Phases Model and the stages of the SECI Model, as well as an evidence mapping of knowledge creation in the cooperation agreements studied. In addition, this work resulted in a descriptive report of the knowledge and cooperation environments in the studied agreements; a quantitative summary of the cooperation agreement documents; along with a framework and a document flow proposal for cooperative actions within UTFPR, or similar institutions, as well as those organizations whose main objective is the generation and sharing of new knowledge.